Hethitisches etymologisches glossar - Tischler, Johann. (Innsbruck Innsbruck Innsbruck Innsbruck Innsbruck)
<5> cilt (1. c. xxiv, 702 sayfa ; 2,1. c. vi, 679 sayfa ; 2,2. c. sayfa [681]-1238 ; 3. c. [1], 505 sayfa ; 4. c. 814 sayfa)